The association between obesity and irritable bowel syndrome among a sample of patients attending the primary health care centers in Erbil city - Mustafa Mahmood , Zana; Hawez Sulaiman , Karwan (Diyala Journal of Medicine, 2022)
Background: Irritable bowel syndrome and obesity are two prevalent conditions in our community which may be associated with each other according to some literature. Both have significant impact on the community. Objective: To find the prevalence of irritable bowel syndrome, its association with general and central obesity, as well as to find its sociodemographic characteristics, and effect of some personal health habits on it. Patients and Methods: In this cross-sectional study, a sample of 248 subjects, 105 males and 143 females, who attended two primary health care centers was taken (included healthy looking subjects and patients with irritable bowel syndrome according to Rome IV criteria). Subjects were aged between 18-65 years. Sociodemographic characteristics, personal health habits, central obesity index and body mass index also recorded in the survey. Results: Prevalence of irritable bowel syndrome was 33.5%, male to female ratio was 0.73:1. No significant association was found between irritable bowel syndrome and general or central obesity. Bad sleep pattern was found to have a significant association with the disorder. Conclusion: The study do not find significant association between obesity and irritable bowel syndrome.